Level of Satisfaction with the Learning Environment and Transition to Employment among Health Professions Graduates at a Ugandan Medical School - Joseph Ngonzi; Timothy Mwanje Kintu; David Jolly Muganzi; Tonny Kyagambiddwa; Lorna Atimango; Raymond Bernard Kihumuro; Francis Bajunirwe (Hindawi Limited, 2024)
Background. To ensure training quality, medical training institutions must provide an adequate learning environment and prepare trainees for work but there is research paucity on the subject. We determined the level of satisfaction with the learning environment and transition to employment among graduates of a Ugandan medical school. Materials and Methods. We conducted an online cross-sectional survey among graduates of Mbarara University of Science and Technology medical school in Uganda, graduating between 1995 and 2020 between March and November 2022. We used Likert scales to measure satisfaction with the learning environment and assessed relevance of the training in transition to the job market. Participants were reached by snowballing and data were analyzed using R-Studio. Results. A total of 361 graduates responded to the survey. Majority were male (72%) and reported having formal employment (94%). Most (57.4%) of the graduates were satisfied with the quality of teaching at medical school. In contrast, fewer graduates (31.2%) were satisfied with the state of the infrastructure at the university and the opportunities available to influence medical school policy such as inclusion on key medical school governance committees. Majority (85%) utilized the knowledge and skills acquired at university in their current job and 75% were satisfied with their ability to perform well under pressure. However, only 37% and 25.4% reported that the medical school supported them in internship and employment search. Conclusion. Students were satisfied with the teaching quality at the university and their ability to perform well at their jobs. However, gaps exist in infrastructure and preparation for transition to jobs. Hence, a need to improve infrastructure.